Juridical Review of Supreme Court Ruling Number 7/Pdt.Sus.HAKI/2021/PN Smg - Ali Mukti Nur Hidayat; Aidul Fitriciada Azhari (Universitas Muhammadiyah Surakarta, 2023)
The importance of brands as a differentiator to avoid imitation is growing as a result of the increasing number of imitations that occur as a result of increasingly advanced trade and wider marketing reach, so that legal protection for brands is increasing. The analytical method uses a literature study. The discussion of the findings of this study is based on the opinions of legal experts and relevant academic journals. This study shows that in a declarative system, the priority of brand rights is determined based on the date of first use. Consequently, the system provides protection even to those who do not officially register their trademarks, allowing them to claim the first use at any time. As stated in its previous ruling, the Tribunal concluded that the two marks have disconcerting similarities in form, composition, combination, elements, sound, sound and appearance. Because PT Surabaya Top and Teh conveyed identical visual, phonetic and conceptual impressions, the group decided that the two were basically identical. The conclusion of this study is that the judge's a quo decision was based on the fact that all elements of similarity exist in the principal and the entire JAGUAR brand which causes harm to the plaintiff, even though his business processes and work are in conflict with the company he named himself which cannot be taken carelessly by others.